Sustainable utilization of CO2toward a circular economy: Prospects, challenges, and opportunities - Ayodele B.V.; Mustapa S.I.; Alsaffar M.A.; Vo D.-V.N. (Elsevier, 2023)
The continuous utilization of fossil fuels for various processes based on the linear economic model will in no small measure constantly increase the concentration of greenhouse gases in the atmosphere. Carbon dioxide (CO2), which accounts for the largest proportion of greenhouse gases, has been a major concern globally which has prompted the calls for urgent actions that could mitigate the emissions of CO2. In this chapter, the prospects, challenges, and opportunities for sustainable utilization of CO2 toward a circular economy are presented. Processes such as CO2 reforming of hydrocarbons and biomass as well as CO2 hydrogenation have been reported as promising technological pathways that could be employed for sustainable utilization of CO2 to produce renewable fuels and value-added products. Despite the various opportunities available for sustainable CO2 utilization, the scale-up of the process is still constrained with various challenges that can be overcome by technological innovations, as well as advances in research and development. 2022 Elsevier B.V. All rights reserved.